Rural credit for aquaculture: an analysis of the Constitutional Financing Fund of the North of Brazil in the State of Pará - Araújo, Janayna Galvão de; Santos, Marcos Antônio Souza dos; Rebello, Fabrício Khoury; Oliveira, Cyntia Meireles de; sousa, Andréia Damasceno Costa de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The article assesses the process of credit granting by the Constitutional Financing Fund of the North of Brazil(FNO) for aquaculture in the State of Pará. The data were obtained from official publications of Banco da Amazônia and interviews with managersof the institutions involved with credit policy. Only after 2000 that the programs and specific lines of credit to meet the demands of aquaculture projects became part of FNO credit plans. Before, the demandsfor investments were met by credit lines that financed any agricultural projects. Between 2000 and 2010 only 0.93% of FNO resources used in the agricultural sector were committed to aquaculture. For the credit managers, the low volume of resources used in aquaculture contrasts with the potential of the activityand results from the combination of factors, such as the low level of organization of the sector, incipient technical assistancewith little expertise in aquaculture, excessive delay in environmental licensing, as well too much bureaucracy to contract operations. It is necessary a greater articulation between the players ofthe aquaculture productive chain to make it viable strategies of resource allocations and encourage the development of the activity in the State of Pará.